Solitary ovarian cancer cells in the peritoneum: What happens below the surface? - Laura M.C. Vos; Willemien J. van Driel; Gabe S. Sonke; Juliette O.A.M. van Baal; Koen K. van de Vijver; Cornelis J.F. van Noorden; Christianne A.R. Lok (Advances in Cancer Biology - Metastasis, 2022)
Background: In advanced epithelial ovarian cancer (EOC), the peritoneum is the primary site of disease recurrence which occurs in >75% of patients despite complete cytoreductive surgery (CRS) and chemotherapy. Macroscopically undetectable remaining cancer cells are deemed to be a source for recurrent disease. We investigated characteristics of occult disease in biopsies of macroscopically normal peritoneum during CRS. Materials and methods: We included 14 patients with advanced stage high grade serous ovarian cancer (HGSOC). Eleven patients had received neoadjuvant chemotherapy (NACT) and three patients were chemotherapy naïve. Each patient underwent three study-related peritoneal biopsies: 1) of a metastasis, 2) adjacent to a metastasis and 3) at distance from metastases. Cryostat sections were immunohistochemically stained for PAX8 and PanCK as markers of EOC cells and for CD31 as a marker for vascular and lymphatic endothelium. The sections were analyzed semi-quantitatively. Results: Macroscopically normal peritoneum showed solitary PAX8-positive cells adjacent to and at distance from metastases in all patients. Thirteen percent of these PAX8-positive cells were found to be attached to the mesothelium and are presumably spread through intra-abdominal fluid. Eighty-seven percent of the solitary PAX8-positive cells were found in the stroma underneath the mesothelium, of which 59% were firmly attached to endothelium and 33% were found in the stroma. In most cases, no sign of proliferation of the solitary cells was observed. Only a few clusters of PAX8-positive cells were found. Chemotherapy did not affect these results. Conclusions: Solitary PAX8-positive cells are present in the macroscopically healthy-looking peritoneum of all EOC patients investigated, irrespective of the distance to macroscopically-visible metastases and of previous treatment. The majority of these solitary cancer cells were attached to endothelium of capillaries, venules or lymphatic vessels. Their solitary character and lack of proliferation suggests a dormant state, which could explain why these cells are unaffected by neo-adjuvant chemotherapy.